2017
DOI: 10.1002/chem.201605458
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Assembly of AIE‐Active Achiral Molecules: An Odd Effect in Self‐Assembly

Abstract: The induction of chirality in supramolecular structures through hierarchical self-assembly of achiral compounds and the control of their handedness are closely related to the evolution of life and the chiral amplification found in nature. Herein, it is shown that the combination of achiral tetraphenylethylene, an aggregation-induced emission (AIE)-active luminophore bearing four alkyl chains with an odd or even number of carbon atoms via an amide linkage in the molecular structure allows the induction and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Together, these interactions prevented crystallization and induced the directional growth of a twisted superstructure (Figure a). Interestingly, they also found that odd or even numbers of carbon atoms led to opposite chiral superstructures, with right‐handed supramolecular structures produced with even‐numbered carbon chains and left‐handed supramolecular structures with odd‐numbered ones . This is because the different alkyl chain length produced a geometric difference in alignment to maximize the van der Waals interactions (Figure b).…”
Section: Endowing Aie Molecules With Self‐assembly Ability Through Momentioning
confidence: 99%
“…Together, these interactions prevented crystallization and induced the directional growth of a twisted superstructure (Figure a). Interestingly, they also found that odd or even numbers of carbon atoms led to opposite chiral superstructures, with right‐handed supramolecular structures produced with even‐numbered carbon chains and left‐handed supramolecular structures with odd‐numbered ones . This is because the different alkyl chain length produced a geometric difference in alignment to maximize the van der Waals interactions (Figure b).…”
Section: Endowing Aie Molecules With Self‐assembly Ability Through Momentioning
confidence: 99%
“…We demonstrate that the combination of achiral tetraphenylethene, an aggregation‐induced emission (AIE)‐active luminophore, bearing four even‐ or odd‐long alkyl chains via amide linkages in the molecular structure, allows the entire process of induction and control of supramolecular chirality into well‐defined helical superstructures by solvophobic control . TEM and SEM images confirm that these twisted ribbons are indeed formed by right‐ and left‐handed helices with an even or odd number of carbon in the alkyl chains, respectively.…”
Section: What Are the Critical Issues And What Are The Future Perspecmentioning
confidence: 99%
“…This inspiringd iscovery can alleviate the notorious ACQ effect of emitters, paving an alternative route for preparing efficient fluorescento rganic materials in the solid state. In addition to silole, many other organic compounds with AIE characteristics have been developed so far,s uch as tetraphenylethene (TPE) [6][7][8][9][10][11][12][13] and aryl-substituted pyrroles. [14][15][16][17] Luminogens with AIE features have been defined as AIEgens by Tang.…”
Section: Introductionmentioning
confidence: 99%